A daily indicator of economic growth for the euro area. (2017) - Aprigliano, Valentina; Foroni, Claudia; Marcellino, Massimiliano; Mazzi, Gianluigi; Venditti, Fabrizio
In this paper, we study alternative methods to construct a daily indicator of growth for the euro area. We aim for an indicator that (i) provides reliable predictions, (ii) can be easily updated at the daily frequency, (iii) gives interpretable signals, and (iv) it is linear. Using a large panel of daily and monthly data for the euro area we explore the performance of two classes of models: bridge and U-MIDAS models, and different forecast combination strategies. Forecasts obtained from U-MIDAS models, combined with the inverse MSE weights, best satisfy the required criteria.